Adults with sensorimotor disorders: enhanced physiological and psychological development following specific sensorimotor training - Niklasson, Mats; Rasmussen, Peder; Niklasson, Irene; Norlander, Torsten (Frontiers in Psychology, 2015)
The aim of the study was to investigate, for the first time, if it is possible to integrate primary reflexes in adults with sensorimotor disorders through sensorimotor therapy. Participants consisted of 14 adults, 1 man and 13 women, with an average age of 35 years who completed a sensorimotor therapy program over three years. They were compared with a reference group of 100 youngsters spanning from 11 to 17 years. Procedures were the same for both youngsters and adults including regular visits to a therapist and training approximately 15 minutes each day at home throughout therapy. Assessments of sensorimotor abilities were made before and after the therapy. Results showed significant improvements on all measurements with regard to treatment for both age groups and the main picture indicated small differences between age groups. After therapy adults were better on balance and orientation tests while the youngsters performed better on sports related gross motor movements, processing of speech sounds and had acquired a better relation between visual skills and vestibular function. Conclusions were that motor problems do not disappear with age and that the same diagnostic instruments and treatment methods can be used for both children and adults with sensorimotor difficulties.